In Silico Analysis of the Minor Histocompatibility Antigen Landscape Based on the 1000 Genomes Project - Bykova, Nadia A.; Malko, Dmitry B.; Efimov, Grigory A. (Frontiers in Immunology, 2018)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is routinely used to treat hematopoietic malignancies. The eradication of residual tumor cells during engraftment is mediated by donor cytotoxic T lymphocytes reactive to alloantigens. In the context of HLA-matched transplantation alloantigens are encoded by various polymorphic genes situated outside of the HLA locus, so-called minor histocompatibility antigens (MiHAs). Recently MiHAs have been recognized as promising targets for posttransplant T-cell immunotherapy, as they have several appealing advantages over tumor-associated antigens (TAAs) and neoantigens. Namely, they are much more numerous than TAAs potentially allowing for multiple targeting in various combinations; unlike neoantigens, they are encoded by germline polymorphisms, some of which are common and thus suitable for off-the-shelf therapy. The genetic sources of MiHAs are nonsynonymous polymorphisms that cause differences in the recipient and donor proteomes and, subsequently, the immunopeptidomes. Systematic description of the alloantigen landscape in HLA-matched transplantation is still lacking as previous studies focused on a few most immunogenic and most common MiHAs. Here we perform thorough in silico analysis of public genomic data to classify genetic polymorphisms that lead to MiHA formation and estimate the number of potentially available MiHA mismatches. Our findings suggest that in a donor/recipient pair there are expected at least several dozen mismatched strong MHC-binding SNP-associated peptides per each HLA allele (116±26 and 65±15 for non-related pairs and siblings respectively in European population as predicted by two independent algorithms). Over 70% of them are encoded by relatively frequent polymorphisms (minor allele frequency>0.1), and thus might be targetable by off-the-shelf therapeutics. The most appealing targets (probability of mismatch over 20%) lay in asymmetric allele frequency region that spans from 0.15 to 0.47, which corresponds to an order of several hundred (213±47) possible targets per HLA allele to be considered for validation of immunogenicity. Overall, these findings demonstrate the significant potential of MiHAs as targets for T-cell immunotherapy and emphasize the need for systematic discovery of novel MiHAs.